Functions of the state in light of the purpose of sharee'ah - El-Seoudi, Abdel Wadoud Moustafa Moursi; Mohd Nor, Amir Husin; Muhammad Husni, Ahmad; Omar, Anwar Fakhri; Laluddin, Hayatullah; Ibrahim, Ibnor Azli; Samsudin, Muhammad Adib; Alias, Muhammad Nazir (Medwell Journal, 2012)
The Islamic state has always been the center of the political analysis even some see that it is the essence of studies on politics. At this age, political studies neglected this subject. The research at hand aims at developing a study on the Islamic state. Any study about the Islamic state must touch on state functions as the state with its history and different models seek to achieve certain functions. Researchers used in this study the inductive approach through extrapolating the jobs of the Islamic state throughout the history of Islam in the past and present times. Also, the researchers relied on the analytical approach through analyzing the historical facts of the functions of the Islamic state, especially in the modern age. Researchers concluded at the end of the research a number of scientific results, most notably: The responsibilities of the Islamic state, regardless of its contents are determined by some beliefs and political ideologies. These responsibilities differ from a country to another depending on the difference of faiths and ideologies. It can be said that there are collective doctrinal rules that set the content and ideological dimensions of these functions and control its inside and outside activities. Scholars of political thought in Islam in its early centuries stated that Sharee‘ah is a methodology for administering worldly life or behavior and handling the conditions and turnings of life. Sharee‘ah should be the scale and reference of all matters of worship and worldly behavior. Based on that, the functions of Islamic state centralize on the establishment of Islamic Sharee‘ah and the application of its rulings in the Muslim community.